Solvability conditions and general solution for mixed Sylvester equations - Wang, Qing-Wen; He, Zhuo-Heng (Automatica (Oxford), 2013)
In this paper, we give some necessary and sufficient solvability conditions for the mixed Sylvester matrix equations, and parameterize general solution when it is solvable. Moreover, we investigate the maximal and minimal ranks of the general solution, and maximal and minimal ranks and inertias of Hermitian part of solution, respectively.